Laryngohyoid fractures in suicidal hanging: A prospective autopsy study with an updated review and critical appraisal - Zátopková, Lenka; Janík, Martin; Urbanová, Petra; Pažinová, Jitka; Hejna, Petr (Forensic science international, 2018)
Laryngohyoid fractures in hanging victims are one of the most studied and paradoxically contradictory topics in forensic pathology. According to literary sources, the incidence of laryngohyoid fractures in hanging varies significantly, from 0% to 100%. To verify the diagnostic significance of these injuries in hanging, we prospectively and consecutively analyzed the occurrence of laryngohyoid fractures in a group of 178 suicidal hanging victims (M/F=150/28, aged 14-94years, mean age=50, complete suspension=111 cases, partial suspension=67 cases) in relation to selected variables (age, sex, weight, the completeness of body suspension, and ligature knot location). Altogether, we identified the following types of laryngohyoid fractures in 129 of 178 cases (72.5%): isolated fracture(s) to the thyroid cartilage in 60 cases (33.7%), combined thyrohyoid fractures in 41 cases (23.0%), isolated fracture(s) to the hyoid bone in 28 cases (15.7%), and no fractures to the cricoid cartilage or the cervical vertebrae. The highest frequency of laryngohyoid fractures was found in lateral hangings (right lateral: 26/34, 76.5%; left lateral: 31/37, 83.8%), whereas the lowest rate was found in anterior hangings (4/11, 36.4%). In lateral hangings, fractures more often occurred contralaterally to the suspension point. Statistical analysis revealed significant associations of the occurrence of laryngohyoid fractures with the age of the victim (p=0.028), with the position of the ligature knot on the neck (p=0.019) and with the age-corrected weight of the victim (p=0.026). In addition, we performed a systematic updated review and critical appraisal of relevant literary sources to report the incidence, fracture patterns, and contributing variables of laryngohyoid injuries in hanging. Both the results of our study and the provided literary synthesis show that if evaluated properly, laryngohyoid fractures in hanging may diagnostically offer far more than just evidence that injury to the neck occurred and may also present research opportunities regarding several issues that should be further analyzed and explained.
Keywords: dospělí; Suicide; fraktury kostí; Sex Distribution; Female; rozložení podle pohlaví; Age Factors; Asphyxia; Adult; Neck Injuries; ženské pohlaví; mladý dospělý; Adolescent; věkové faktory; lidé; Fractures, Bone; Fractures, Cartilage; Forensic Pathology; Aged, 80 and over; sebevražda; Laryngeal Cartilages; laryngeální chrupavky; Middle Aged; poranění krku; tělesná hmotnost; Age Distribution; prospektivní studie; Hyoid Bone; Male; Aged; Czech Republic; Prospective Studies; Young Adult; věkové rozložení; Body Weight; os hyoideum; Česká republika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; chondrální fraktury; asfyxie; mladiství; soudní patologie; Humans